The Ambiguity Commune of The Novel “The Magic Mountain”: Social Class Tensions and Inquiry of Self - On, Thi My Linh (International Journal of Language and Literary Studies, 2024)
This article aims to delve into the assertion of social and personal change at the dawn of World War I as reflected in Thomas Mann’s novel The Magic Mountain. Hans Castorp, the central character, undergoes a profound journey of experience and growth, which is divided into two stages: before and after his stay at the sanatorium. Initially depicted as a young man engrossed in leisure and superficial pursuits, indifferent to societal changes and personal pleasures, Hans undergoes a significant transformation during his time at the sanatorium. This period sparks deeper intellectual and moral engagement, mirroring T.Mann’s vision for the elite class in early 20th-century German society. T.Mann envisioned a shift from apathy and detachment to active involvement with the community and a clearer sense of purpose. Through Hans Castorp, T.Mann explores the potential for personal and societal renewal. This study employs literary textual analysis to examine Hans Castorp’s unique characteristics, contradictions, and development, providing insights into the evolution of T.Mann’s artistic and philosophical ideas. By analyzing Hans’s character, this research highlights T.Mann’s critique of his contemporary society and his hope for a more engaged and purposeful elite. It underscores the enduring relevance of The Magic Mountain in exploring themes of personal growth and social transformation.